Characterization of soybean cyst nematode diversity in Kansas - Rzodkiewicz, Pamela Ann (Kansas State University, 2010)
The soybean cyst nematode (Heterodera glycines) (SCN) is an important pathogen of soybean in the United States. Annual yield losses from SCN are estimated to be over $2 billion worldwide. However, SCN virulence or the ability of a nematode to grow on resistant soybean genotypes varies widely among SCN populations. Fortunately there are several genetic sources of resistance to decrease the virulence of the pathogen on soybean. The objectives of this research were to: 1) characterize the genetic diversity of soybean cyst nematode populations in Kansas, 2) determine the frequency of Kansas SCN populations virulent on PI88788, 3) determine which plant introductions used in the HG Type Test provide the best level resistance, and 4) compare the performance of commercial soybean cultivars to the plant introduction from which their SCN resistance was derived. Soil samples were collected from SCN-infested fields across the state. Each soil sample was taken to the greenhouse and planted to a susceptible soybean cultivar to increase SCN population. Following an SCN population increase, a HG Type Test was planted. H. glycines field populations were highly variable, not only in population densities, but also in their abilities to develop on soybean genotypes. Collected from a diverse range of environments, ten HG types were identified. About 50% of the H. glycines populations were virulent on PI 88788, and most of the populations were virulent on commercial SCN resistant lines which derived their resistance from PI 88788. The commercial lines tended to be more susceptible to SCN than the lines from which they derived their resistance, but few HG populations were virulent on PI 437654 or the commercial line that derived its resistance from PI 437654. These results suggest that sources other than PI 88788 should be used in the development of H. glycines resistant cultivars for Kansas. One possible source of resistance is PI 437654. Information about SCN diversity in Kansas will improve decisions regarding cultivar development and selection for SCN management.
Keywords: soybean cyst nematode; Kansas; heterodera glycines; Agriculture, Agronomy (0285)